Diplomats and diplomacy: assessing the influence of experience in the implementation of U.S. foreign policy - Kidd, Justin Eric (Kansas State University, 2018)
In 2008, Ambassador’s Neumann and Pickering wrote letters to Senator’s Obama and McCain, with recommendations on qualifications for US Ambassador’s. Both Senator’s had recently received their party’s nomination for President, and Neumann and Pickering took the opportunity to suggest qualifications they believed were necessary for US ambassadors to perform their diplomatic tasks better. Their letters suggested that career ambassadors perform better, and they recommended that political appointees be limited to ten percent. The historical average has been roughly thirty percent. They also recommended that ambassadors have previous regional experience, and be knowledgeable about the countries in which they would be assigned, as well as speak the local language. What their letters were missing was evidence these traits actually make a difference in how well ambassadors perform their roles. In fact, this evidence is missing from the extant literature describing ambassadorial roles and responsibilities. This dissertation seeks to quantitatively and qualitatively analyze Neumann’s and Pickering’s qualifications, marking the first time this important subject has been examined using social science methodology.
Keywords: U.S. Ambassador qualification; U.S. foreign policy; Political appointees; Career ambassadors; Assessing U.S. foreign policy; Assessing ambassador performance